Simultaneous All-Optical or and xor Logic Gates Based on the Bimodal Photonic Cavity Containing a Quantum Dot - Han Ye; Shen Ma; Zhongyuan Yu; Yumin Liu; Zhihui Chen (IEEE Photonics Journal)
We theoretically present a design for simultaneous all-optical or and xor logic gates based on single quantum dot (QD)-bimodal cavity system working in low-photon-number regime. The coupling between the QD and two degenerate cavity modes establishes new indirect excitation paths. Driven by single pulsed laser, both mode transmissions are observed. The delay between the peaks of the transmitted pulses is regarded as the extra transition interval (ETI) in the indirect path. When driven by two orthogonally polarized pulsed lasers with delay same as ETI, the coupling system suppresses the latter mode transmission due to the destructive interference effect. The or and xor logic gates based on presence of light are built and the function can be switched between two detectors by simply adjusting the driving pulse sequence. The results show that the proposed logic gates work well within a large range for coupling strength with comparable cavity decay rate. When taking two nonidealities (the detuning between two cavity modes and nonidentical coupling strengths) into consideration, the proposed system shows acceptable tolerances. Moreover, the robustness of the performance on parameters of the driving lasers, including pulse delay, width of pulse, absolute driving strength, and relative driving strength ratio, are demonstrated.